Recent Advances in Graphene-Based Materials for Lithium Batteries - S. Pappas, George; Ferrari, Stefania; Wan, Chaoying (Current Organic Chemistry, 2015)
Energy production and storage have become key issues due to the ever increasing demand of electricity in modern days. Rechargeable batteries are recognized as the primary power sources for applications from portable electronic devices to electric vehicles. Recently, there has been a growing interest in investigating graphene nanocomposite materials for various energy storage applications, such as electrodes in lithium batteries. With its unique structural, mechanical, and electrical properties, graphene can be a critical component in nanostructured electrode materials with improved capacity and cyclability, enabling the development of advanced batteries and new battery technologies. This paper reviews the recent achievements in graphene utilization in negative electrodes for Li-ion batteries and introduces the latest progress of flexible graphene-based Li-ion batteries. A survey of the scientific advances achieved thanks to the use of graphene in the so called “beyond Li-ion” technologies, namely Li-sulphur and Li-O2 batteries, is also presented.
Keywords: graphene